Transport Infrastructure a Key Element of Economic Development in the European Community: The Case of Romania - Daniel F. FISTUNG; Cornelia NEAGU; Marius F.R. BULEARCĂ; Cristian SIMA (Communications of International Proceedings, 2021)
Starting from the de facto situation of the Romanian transport infrastructure and highlighting its place within the European communication network, this study presents the relevant aspects of interconnectivity between infrastructure and general economic development, between regional disparities created by the state of transport networks and the necessary measures to be taken to improve the current situation. The aim is to highlight the possibilities for the modernization and development of transport infrastructures in Romania in line with the requirements of the specific Community policy, in particular with a view to the implementation of a sustainable European transport system and national needs. The analysis revealed that the reliability of the road, rail and waterway infrastructure in Romania is low and its improvement will depend on the efficiency and prioritization of specific projects along with their political and financial support, on short, medium and long terms. Also affected by the health pandemic, the modernization, maintenance and development of transport infrastructures received positive impetus from the European Union through the creation of the Recovery and Resilience Mechanism, to which Romania also accessed financing proposals, requesting significant shares of these funds for infrastructure. Methods of quantitative analysis of documents, statistical analysis of quantitative information, interpretative analysis of data (cumulative analysis of quantitative and qualitative data) and evaluation of processes and results were used in the analysis performed. The main series of statistical data were obtained from national and international (mainly European) institutions and other profile works.
Keywords: Transport infrastructure; Economic development; Transport infrastructure demand and supply; Transport policy; Infrastructure funding.